1988
DOI: 10.1042/bj2520111
|View full text |Cite
|
Sign up to set email alerts
|

Do metal ions promote the re-activation of the 2,3-bisphosphoglycerate-independent phosphoglycerate mutases?

Abstract: It has been reported [Smith, McWilliams & Hass (1986) Biochem. Biophys. Res. Commun. 136, 336-340] that addition of certain metal ions, notably Co2+ and Mn2+, promoted the refolding of denatured phosphoglycerate mutase from wheat germ. We have re-investigated these experiments and have shown that, when precautions are taken to avoid artefacts in the assay system, the metal ions do not promote any re-activation of the denatured wheat-germ or Aspergillus nidulans enzymes. An alternative explanation is offere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
(37 reference statements)
1
5
0
Order By: Relevance
“…[49] also reported relatively low specific activity of PGAM, albeit somewhat higher than in our experiments and dependent on the cell disruption procedure. It has been reported that i‐PGAM of wheat germ and Aspergillus nidulans is rapidly and irreversibly inactivated by metal‐chelating agents such as EDTA [50]. As our trypanosome lysates are usually prepared in isotonic solutions containing EDTA (0.25 m sucrose, 25 m m Tris/HCl, pH 7.4, 1 m m EDTA), we examined the possibility that the low specific activity found in the lysates could be attributed to the action of the chelator.…”
Section: Resultsmentioning
confidence: 99%
“…[49] also reported relatively low specific activity of PGAM, albeit somewhat higher than in our experiments and dependent on the cell disruption procedure. It has been reported that i‐PGAM of wheat germ and Aspergillus nidulans is rapidly and irreversibly inactivated by metal‐chelating agents such as EDTA [50]. As our trypanosome lysates are usually prepared in isotonic solutions containing EDTA (0.25 m sucrose, 25 m m Tris/HCl, pH 7.4, 1 m m EDTA), we examined the possibility that the low specific activity found in the lysates could be attributed to the action of the chelator.…”
Section: Resultsmentioning
confidence: 99%
“…Cofactor-independent phosphoglycerate mutase is active as a monomer which is much larger (Mr about 60,000) than the subunit of the cofactor-dependent enzyme. The cofactor-independent mutase has proved to be more difficult to purify than the cofactor-dependent enzymes, and this may relate to its inherent instability (McAleese et al, 1985;Johnson and Price, 1988), especially at low pH (Botha and Dennis, 1986). The absence of primary structure information describing cofactor-independent phosphoglycerate mutase means that it is unclear whether the cofactordependent and -independent forms of the enzyme have diverged from a common ancestor.…”
Section: B Cofactor-independent Monophosphoglycerate Mutasesmentioning
confidence: 99%
“…Thus, for example, Leadlay et al (1977) and Smith and Hass (1985) noted multiple forms of phosphoglycerate mutase during purification from wheat germ without attributing this to the presence of isoenzymes. Recent work to study cofactor-independent phosphoglycerate mutase from Aspergillus nidulans (Johnson and Price, 1988) and from Neurospora crassa (McAleese et al, 1988) indicates that filamentous fungi may be rather more straightforward sources of homogeneous enzyme.…”
Section: Isoenzymesmentioning
confidence: 99%
“…13,15,20,[41][42][43] However, the tyrosine is not present in bacterial iPGAMs, 5,36,[44][45][46] nor in nematode, 19 fungal, or algal enzymes. 15,20 It is tempting to suggest that two classes of iPGAM exist that differ with respect to metal binding properties, depending on the presence or absence of this tyrosine. Available biochemical information concerning sensitivity to chelators and reactivation by divalent metal ions is consistent with this hypothesis.…”
Section: Differences Between the Lm Ipgam And Bs Ipgam M2 Sitesmentioning
confidence: 99%
“…8 Phosphoglycerate mutase catalyses the interconversion of 2-phosphoglycerate (2PG) and 3-phosphoglycerate (3PG) in the glycolytic and gluconeogenic pathways. The cofactor-independent enzyme iPGAM is active in the absence of the cofactor 2,3-bisphosphoglycerate and is found in several protozoa including T. brucei 9,10 and Leishmania mexicana, 6,7 as well as in plants [11][12][13][14][15][16][17][18] and representatives of nematodes, 19 fungi, 15,20 algae, bacteria, 5,21 and archaea. 22,23 All experimentally characterised iPGAMs from eubacteria, plants, and invertebrates are monomers with a molecular mass of 55,000-75,000 Da.…”
Section: Introductionmentioning
confidence: 99%